Action of serum on the output of secretory glycoproteins from human bronchi in vitro. - Williams, I P (1983)
The effect on mucin output of placing dilute serum from healthy donors in contact with the luminal surface of human airway has been studied. Bronchi were dissected from lungs removed at operation. Mucins, radiolabelled biosynthetically, were collected from the luminal aspect of the bronchi, which were mounted in Ussing chambers. Serum added to the luminal aspect of the tissue, at dilutions ranging from 1:100 to 1:10 of Krebs-Henseleit solution, consistently increased the output of radiolabelled mucins. The concentrations of serum tested in these experiments lie within the range commonly found in sputum coughed from the lungs of those with inflamed airways. Serum diluted to 1:2500, which is roughly the concentration found in the normal human airway, had little or no effect on bronchial secretion. Increased leakage of serum into the inflamed airways is suggested as one of the stimuli that increase bronchial secretion.